Innovation in Numeracy Literacy through Educational Board Games: An Innovation in Elementary Mathematics Learning - Motinggo, Yoserizal (International Journal of Curriculum Development, Teaching and Learning Innovation, 2025)
This research investigates the use of educational board games as an innovative approach to improve numeracy literacy learning in elementary schools. The problem addressed in this study is the low level of numeracy skills and limited motivation among students in learning mathematics. The objective is to evaluate the effectiveness of integrating board games into classroom instruction to enhance both academic and socio-emotional outcomes. The study employed a qualitative-descriptive design with classroom implementation. Data were collected through observations, student performance assessments, and teacher feedback to analyze the impact of board game based learning. The results show that students demonstrated notable improvements in numeracy skills, including counting, arithmetic operations, and problem-solving. Moreover, the use of board games increased motivation, participation, and positive attitudes toward mathematics. Collaborative play further supported the development of social interaction and problem-solving abilities, enriching the overall learning process. In conclusion, educational board games are an effective and engaging method for enhancing numeracy literacy while fostering student motivation and collaborative skills. This research highlights their potential as a sustainable innovation in elementary education, contributing to both academic success and holistic student development.